AKTIVITAS PEMBELAJARAN MENDALAM BERBASIS BUDAYA BATAK TOBA DAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SMP - Imelda, Imelda; Sagala, Masdiana; Manurung, Audy Sihol Marito (MES: Journal of Mathematics Education and Science, 2025)
his study aims to describe Batak Toba culture-based deep learning activities combined with differentiated learning in improving junior high school students' higher order thinking skills (HOTS). This study is descriptive qualitative with a case study approach. The research subjects were 26 eighth-grade students at Budi Murni 3 Junior High School in Medan who participated in learning activities using three types of Batak Toba culture-based worksheets on the material of discovering and proving the Pythagorean theorem in accordance with the students' ability levels. Data were collected through observation of student activities, student work results, and final tests, then analysed based on HOTS indicators: analysis, evaluation, and creation. The results showed that the learning activities went very well with a student engagement rate of 95%. The integration of Batak Toba culture, particularly the Ulos motif, helped students understand the abstract concept of the Pythagorean theorem more concretely, while differentiated learning provided space for students with different abilities to develop according to their potential. Thus, deep learning based on local culture, combined with effective differentiation, is effective in improving HOTS while supporting the implementation of the Merdeka Curriculum.